Characteristics of Gelatin from Tilapia (Oreochromisniloticus) Bones Soaked Using Pineapple Liquid Extract (Ananascomosus L. Merr) - Simbolon, Sarwoedy; Edison, Edison; Ilza, Mirna (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT This study aims to find out the chemical and physical characteristics of gelatin from tilapia bone soaked using pineapple liquid extract. Pineapple fruit is known to contain citric acid that is quite high.The research method used in this study is an experimental method by pre-treatment (soaking) of fish bones in liquid extracts of pineapples using different times. G20 (soaking of fish bones in pineapple liquid extract for 20 hours), G30 (soaking of fish bones in pineapple liquid extract for 30 hours) and G40 (soaking of fish bones in pineapple liquid extract for 40 hours).The analysis parameters in this study are SDS-PAGE values, sensory analysis, viscosity, pH values, moisture and ashcontent.The results of this study showed that gelatin extract of tilapia bone with soaking (demineralization process) using liquid extract with pineapple fruit at different times, produces SDS-PAGE value (molecular weight of gelatin protein 80 kDa, 60 kDa, and 50 kDa),sensory characteristics that meet the standards (yellowish-white powder form, smells of weak fish and tasteless), viscosity (1.39-1.52 cP), The physical properties of pH (5.06-5.26), chemical properties namely moisture content (4.54-6.47%), ash content (7.65-10.25%. The best treatment was obtained in the pre-treatment (soaking) of tilapia fish bones within 40 hours with liquid extract of pineapple fruit.Keywords: soaking, fishbones, pineapple liquid extract, gelatin